Cloning, Characteristics, and Functional Analysis of Rabbit NADPH Oxidase 5 - Chen, Feng; Yin, Caiyong; Dimitropoulou, Christiana; Fulton, David J. R. (Frontiers in Physiology, 2016)
Background: Nox5 was the last member of the Nox enzyme family to be identified. Functionally distinct from the other Nox isoforms, our understanding of its physiological significance has been hampered by the absence of Nox5 in mouse and rat genomes. Nox5 is present in the genomes of other species such as the rabbit that have broad utility as models of cardiovascular disease. However, the mRNA sequence, characteristics and functional analysis of rabbit Nox5 has not been fully defined and were the goals of the current study. Methods: Rabbit Nox5 was amplified from rabbit tissue, cloned and sequenced. COS-7 cells were employed for expression and functional analysis via Western blotting and measurements of superoxide. We designed and synthesized miRNAs selectively targeting rabbit Nox5. The nucleotide and amino acid sequences of rabbit Nox5 were aligned with those of putative rabbit isoforms (X1, X2, X3, and X4). A phylogenetic tree was generated based on the mRNA sequence for Nox5 from rabbit and other species. Results: Sequence alignment revealed that the identified rabbit Nox5 was highly conserved with the predicted sequence of rabbit Nox5. Cell based experiments reveal that rabbit Nox5 was robustly expressed and produced superoxide at rest and in a calcium and PMA-dependent manner that was susceptible to superoxide dismutase and the flavoprotein inhibitor, DPI. miRNA-1 was shown to be most effective in down-regulating the expression of rabbit Nox5. Phylogenetic analysis revealed a close relationship between rabbit and armadillo Nox5. Rabbit Nox5 was relatively closely related to human Nox5, but lies in a distinct cluster. Conclusion: Our study establishes the suitability of the rabbit as a model organism to further our understanding of the role of Nox5 in cardiovascular and other diseases and provides new information on the genetic relationship of Nox5 genes in different species.